How Is Mass Spectrometry Tackling the COVID-19 Pandemic? - Ibáñez, Alfredo J. (Frontiers in Analytical Science, 2022)
Most of us have never faced a pandemic before. The World Health Organization declared the 2019 novel coronavirus infectious disease (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2 virus), a pandemic by March 11th, 2020. Today, this illness has reported more than 5’331,019 fatalities worldwide (December 17th, 2021). The COVID-19 pandemic has posed an unprecedented global challenge and put the academic community on “the spot.” The following mini-review reports how the MS community improved the understanding of the SARS-CoV-2 virus pathophysiology while developing diagnostic procedures to complement the PCR-based approaches. For example, MS researchers identified the interaction sites between the SARS-CoV-2 virus and their hosts; this new knowledge is critical for developing antiviral drugs. MS researchers also realized that COVID-19 should be considered a systemic disease and not just a respiratory illness since its metabolic, lipidomic, and proteomic profile reflects four different clinical disorders: (i) acute inflammatory response, (ii) a cardiovascular disease, (iii) a prediabetic/diabetes and (iv) liver dysfunction. Furthermore, MS researchers put forth the knowledge that the metabolic and lipidomic profile of several patients remained altered after being discharged, thus hinting at the scientific basis for the long COVID syndrome.